Prevalence of trachoma in the area councils of the Federal Capital Territory, Nigeria: results of six population-based surveys. (28th December 2018) - Muhammad, Nasiru; Mpyet, Caleb; Adamu, Mohammed Dantani; William, Adamani; Umar, Murtala Muhammad; Muazu, Habila; Onyebuchi, Uwazoeke; Isiyaku, Sunday; Flueckiger, Rebecca M.; Chu, Brian K.; Willis, Rebecca; Pavluck, Alex; et al.
ABSTRACT: Purpose : The World Health Organization's (WHO's) global trachoma elimination programme recommends mapping of trachoma at district level for planning of elimination activities in affected populations. This study aimed to provide data on trachoma prevalence for the Area Councils of Nigeria's Federal Capital Territory (FCT). Methods : Using the Global Trachoma Mapping Project (GTMP) protocols, in March and April 2014, we conducted a population-based cross-sectional survey in each of the six Area Councils of FCT. Signs were defined based on the WHO simplified grading scheme. Results : 98% to 100% of the targeted households were enrolled in each Area Council. The number of children aged 1–9 years examined per Area Council ranged from 867 to 1248. The number of persons aged ≥15 years examined ranged from 1302 to 1836. The age-adjusted prevalence of trachomatous inflammation—follicular in 1–9-year-olds was <5% in each Area Council. The age- and gender-adjusted prevalence of trichiasis in those aged ≥15 years ranged from 0.0% to 0.3%; two Area Councils (Gwagwalada and Kwali) had prevalences above the 0.2% elimination threshold. The proportion of households with access to improved latrines and water sources ranged from 17 to 90% and 39 to 85% respectively. Conclusions : Gwagwalada and Kwali Area Councils need to perform more trichiasis surgeries to attain the trichiasis elimination prevalence target of 0.2% in persons aged ≥15 years. No Area Council requires mass antibiotic administration for the purposes of trachoma's elimination as a public health problem. All Area Councils need to accelerate provision of access to improved water sources and latrine facilities, to achieve universal coverage.